Integrating Technology to Elevate the Pedagogical Skills of Islamic Religious Educators - Nurhaizan Sembiring (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: The digital era demands Islamic Religious Education (PAI) teachers not only master religious content but also effectively integrate technology to enhance learning quality. This study aims to explore how technology is incorporated into PAI teacher competency development programs under the North Sumatra Regional Office of the Ministry of Religious Affairs, and to identify associated challenges and opportunities. Methodology: Using a qualitative approach, data were collected through interviews, observations, and document analysis involving teachers, trainers, and program officials. Thematic analysis was applied to capture experiences and patterns in technology use during training. Main Findings: Findings indicate that technology integration has positively impacted teachers’ pedagogical and digital competencies. Tools like Google Classroom and LMS platforms are increasingly used. However, challenges remain, such as limited infrastructure, uneven digital literacy, and overly theoretical training modules. Novelty/Originality of this study: The COVID-19 pandemic served as a catalyst for digital adaptation. Yet, sustainable improvement requires more practical, needs-based training strategies, infrastructure support, and collaboration among stakeholders. A localized integration model is proposed to align digital transformation with the contextual needs of Islamic education.